Bipolar current collector and preparation method thereof, bipolar electrode and battery

By designing bipolar current collectors, including base film layer, ceramic layer, aluminum layer and copper layer, and forming micro channels through laser drilling, the problem of difficult alignment of lithium battery pole sheets and separators is solved, and the battery energy density improvement and production efficiency simplification is achieved.

CN120164956APending Publication Date: 2025-06-17YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510341258.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-06-17

AI Technical Summary

Technical Problem

During the production process of lithium batteries, the alignment and coverage allowance of the pole sheet and diaphragm are difficult to control, which affects the entire life cycle of the battery. The special structure of the bipolar pole sheet makes it difficult to induce current, and the diaphragm still needs to exist.

Method used

A bipolar current collector is designed, including a base film layer, a ceramic layer, an aluminum layer and a copper layer, and micro channels are distributed along the thickness direction, eliminating the separator structure, and forming channels through laser holes, improving battery energy density and production efficiency.

Benefits of technology

It significantly improves the battery volume energy density, reduces the battery internal resistance, improves the rate performance, simplifies the production process, and avoids the risk of short circuit caused by diaphragm alignment errors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120164956A_ABST
    Figure CN120164956A_ABST
Patent Text Reader

Abstract

The invention discloses a bipolar current collector and a preparation method thereof, a bipolar electrode and a battery, the bipolar current collector comprises a base film layer, an aluminum layer is arranged on the surface of one side of the base film layer, and a copper layer is arranged on the surface of the other side of the base film layer; the base film layer comprises a middle polymeric film layer and ceramic layers on the surfaces of the two sides of the polymeric film layer; miniature channels for lithium ions to pass through are distributed on the bipolar current collector along the thickness direction, and the miniature channels penetrate through the aluminum layer, the base film layer and the copper layer. A diaphragm in a traditional bipolar electrode is omitted, so that the volume energy density in the battery is remarkably improved, lithium ions in the battery can have diffusion channels in multiple directions, the internal resistance of the battery is reduced, and the rate capability is improved. According to the invention, a diaphragm lamination process is omitted, the production efficiency can be improved, and meanwhile, the risk of short circuit at the edges of the positive and negative active material layers caused by alignment errors of the lamination process is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a bipolar current collector, a preparation method thereof, a bipolar electrode and a battery. Background Art

[0002] Lithium batteries are produced by alternately arranging the positive electrode sheet, the separator, and the negative electrode sheet, and combining them together in a winding or stacking manner to form a core. In its assembly process, the alignment and wrapping margin of the electrode sheet and the separator become the difficulties in process control and have a great impact on the entire life cycle of the lithium battery.

[0003] Currently, some researchers have proposed a multi-layer bipolar electrode sheet, which includes a polymer base film and copper layers and aluminum layers respectively attached to both side surfaces of the base film. Negative and positive active material layers are respectively coated on the copper layer and the aluminum layer, so as to compound the positive and negative electrodes into a bipolar electrode sheet. This bipolar electrode sheet can effectively improve the energy density of the battery, improve the stacking production efficiency of the battery, and improve the alignment of the electrode sheet and the separator. However, due to its special structure, the extraction of current is more difficult than that of a conventional electrode sheet, and the separator is still required. Summary of the Invention

[0004] Based on the above prior art, the purpose of the present invention is to further optimize the tab structure of the bipolar current collector and the battery assembled therewith, and improve the energy density of the battery and simplify the battery production process.

[0005] To achieve the above purpose, the technical solution provided by the present invention is as follows:

[0006] In the first aspect of the present application, a bipolar current collector is provided, which includes a base film layer, an aluminum layer is provided on one side surface of the base film layer, and a copper layer is provided on the other side surface;

[0007] The base film layer includes a middle polymer film layer and ceramic layers on both side surfaces of the polymer film layer;

[0008] Micro-channels for lithium ions to pass through are distributed in the thickness direction of the bipolar current collector, and the micro-channels penetrate through the aluminum layer, the base film layer and the copper layer.

[0009] In the second aspect of the present application, a preparation method of a bipolar current collector is provided, including the following steps:

[0010] Coat ceramic slurry on both side surfaces of the polymer film, and dry it to obtain a base film layer;

[0011] Prepare a copper layer on one side surface of the base film layer and an aluminum layer on the other side surface to obtain a semi-finished bipolar current collector;

[0012] Perform laser drilling on the semi-finished bipolar current collector so that micro-channels penetrating through the aluminum layer, the base film layer and the copper layer are evenly distributed thereon.

[0013] The third aspect of the present application provides a bipolar electrode, which includes the above bipolar current collector, and further includes a positive electrode active material layer and a negative electrode active material layer. The positive electrode active material layer is disposed on the outer surface of the aluminum layer, and the negative electrode active material layer is disposed on the outer surface of the copper layer;

[0014] The outer surface of the aluminum layer is divided into a positive tab connection area, and no positive electrode active material layer is provided in the positive tab connection area; the outer surface of the copper layer is divided into a negative tab connection area, and no negative electrode active material layer is provided in the negative tab connection area.

[0015] Further, on the surface of the base film layer where the aluminum layer is provided, the aluminum layer only covers a part of the surface of the base film layer, and the area of the base film layer not covered by the aluminum layer exceeds the positive tab connection area; on the surface of the base film layer where the copper layer is provided, the copper layer only covers a part of the surface of the base film layer, and the area of the base film layer not covered by the copper layer exceeds the negative tab connection area.

[0016] The fourth aspect of the present application provides a battery, which includes at least one of the above bipolar electrodes; when there are multiple bipolar electrodes, the bipolar electrodes are stacked in sequence, and the active material layers facing each other between any two adjacent bipolar electrodes are active material layers of the same polarity.

[0017] To optimize the above technical solutions, the specific measures taken also include:

[0018] Among several bipolar electrodes stacked in sequence, the projections of each positive tab connection area on the projection plane perpendicular to the thickness direction of the bipolar current collector overlap, and the projections of each negative tab connection area on the projection plane perpendicular to the thickness direction of the bipolar current collector overlap.

[0019] It further includes tabs, and one tab is shared between any two adjacent bipolar electrodes;

[0020] When the tab connection areas facing each other between adjacent bipolar electrodes are positive tab connection areas, a positive tab is inserted between the two positive tab connection areas, and both sides of the positive tab are connected to the two positive tab connection areas respectively;

[0021] When the tab connection areas facing each other between adjacent bipolar electrodes are negative tab connection areas, a negative tab is inserted between the two negative tab connection areas, and both sides of the negative tab are connected to the two negative tab connection areas respectively.

[0022] Further, the tab is a full tab, and the width of the tab is the same as the width of the bipolar electrode.

[0023] Further, the connection areas between any two adjacent bipolar electrodes and the same tab shared between them do not completely overlap.

[0024] Further, on the projection plane perpendicular to the thickness direction of the bipolar current collector, the active material layers between the tab and the two adjacent bipolar electrodes where the tab is located do not overlap.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0026] In the present invention, the base film layer in the bipolar electrode is designed as a polymer film layer plus ceramic layers on both sides. A copper layer and an aluminum layer are provided on the surface of the base film layer, and the microchannels penetrate through the aluminum layer, the base film layer, and the copper layer. Such a structure can provide current output channels for the positive active material and the negative active material, eliminating the separator in the traditional bipolar electrode; the ceramic layers added on both sides of the polymer film layer can isolate electron transmission, prevent the polymer film layer from easily shrinking after heating, and enhance the bonding strength between the polymer base film and the metal layer.

[0027] The present invention can significantly improve the volume energy density in the battery, and there are multiple diffusion channels for lithium ions in the battery, reducing the internal resistance of the battery and improving the rate performance.

[0028] The present invention eliminates the separator lamination process, which can improve production efficiency and avoid the risk of short circuit at the edges of the positive and negative active material layers caused by alignment errors in the lamination process. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 : Schematic structural diagram of the bipolar current collector of the present invention.

[0030] Figure 2 : Schematic structural diagram of the bipolar electrode of the present invention.

[0031] Figure 3 : Schematic structural diagram of the battery of the present invention.

[0032] Figure 4 : Schematic diagram of the lithium ion diffusion principle during charge / discharge.

[0033] In the figure: 1 - base film layer, 2 - ceramic layer, 3 - aluminum layer, 4 - copper layer, 5 - positive active material layer, 6 - negative active material layer, 7 - microchannel, 8 - negative tab, 9 - conductive adhesive, 10 - positive tab. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0034] The above content of the present invention will be further described in detail below in the form of specific embodiments, but it should not be understood that the scope of the above subject matter of the present invention is limited to the following embodiments. All technologies implemented based on the above content of the present invention belong to the scope of the present invention.

[0035] The experimental methods used in the following examples are all conventional methods unless otherwise specified, and the reagents, methods, and equipment used are all conventional reagents, methods, and equipment in the technical field of the present invention unless otherwise specified.

[0036] The present invention provides a bipolar current collector, as Figure 1 shown, which includes a base film layer 1, an aluminum layer 3 is provided on one side surface of the base film layer 1, and a copper layer 4 is provided on the other side surface;

[0037] The base film layer 1 includes a middle polymer film layer and ceramic layers 2 on both side surfaces of the polymer film layer;

[0038] The bipolar current collector is distributed with micro-channels 7 for lithium ions to pass through in the thickness direction, and the micro-channels 7 penetrate through the aluminum layer 3, the base film layer 1, and the copper layer 4.

[0039] The present invention also provides a preparation method of a bipolar current collector, including the following steps:

[0040] Coat ceramic slurry on both side surfaces of the polymer film, and dry it to obtain the base film layer 1;

[0041] Prepare a copper layer 4 on one side surface of the base film layer 1 and an aluminum layer 3 on the other side surface to obtain a semi-finished bipolar current collector;

[0042] Perform laser drilling on the semi-finished bipolar current collector so that micro-channels 7 penetrating through the aluminum layer 3, the base film layer 1, and the copper layer 4 are evenly distributed thereon.

[0043] The base film layer 1 of the present invention can adopt conventional base film materials in the art, such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.; the thickness of the base film layer 1 can be 2-7 μm.

[0044] The main material types of the ceramic slurry can be selected from alumina, boehmite, silica, titanium dioxide, barium titanate, etc.; the mass proportion of the main material in the ceramic slurry is 50-60%, and the main composition of the ceramic slurry also includes a binder, a dispersant, and a solvent, wherein the binder can be selected from polyvinyl alcohol (PVA) or polyacrylic acid (PAA), and the mass proportion is between 5%-15%; the dispersant can be selected from polyethylene glycol (PEG) or sodium polyacrylate (PAAS), and the mass proportion is between 0.1%-1%; the commonly used solvent is water, and the mass proportion is between 30%-40%.

[0045] The thickness of the ceramic layer 2 after drying the ceramic slurry is 0.6-1.5 μm; the drying time is 1-5 min, and the temperature is 105-120 °C.

[0046] The thickness of the aluminum layer 3 and the copper layer 4 can be 0.8-3 μm.

[0047] The aperture size of the laser drilling can be 1 - 60 μm, preferably 10 - 50 μm;

[0048] Uniformly distributed pores are formed through the drilling, and the pore spacing between adjacent holes is more than 50 μm, such as 100 μm, 300 μm, 600 μm, 1 mm, etc., preferably 80 - 500 μm.

[0049] The present invention also provides a bipolar electrode, such as Figure 2 as shown, which includes the above bipolar current collector, and further includes a positive electrode active material layer 5 and a negative electrode active material layer 6. The positive electrode active material layer 5 is disposed on the outer surface of the aluminum layer 3, and the negative electrode active material layer 6 is disposed on the outer surface of the copper layer 4;

[0050] The outer surface of the aluminum layer 3 is divided into a positive tab 10 connection area, and the positive electrode active material layer 5 is not provided in the positive tab 10 connection area; the outer surface of the copper layer 4 is divided into a negative tab 8 connection area, and the negative electrode active material layer 6 is not provided in the negative tab 8 connection area.

[0051] In some embodiments, the positive electrode active material layer 5 covers the outer surface of the aluminum layer 3 except for the positive tab 10 connection area, and the negative electrode active material layer 6 covers the outer surface of the copper layer 4 except for the negative tab 8 connection area.

[0052] The positive electrode active material and the negative electrode active material can both adopt conventional materials in the art.

[0053] The present invention also provides a battery, which includes at least one of the above bipolar electrodes.

[0054] When there are multiple bipolar electrodes, the bipolar electrodes are stacked in sequence, and the active material layers disposed opposite to each other between any two adjacent bipolar electrodes are active material layers of the same polarity, such as Figure 3 as shown.

[0055] In some embodiments, among several bipolar electrodes stacked in sequence, the projections of the positive tab 10 connection areas on the projection plane perpendicular to the thickness direction of the bipolar current collector overlap, and the projections of the negative tab 8 connection areas on the projection plane perpendicular to the thickness direction of the bipolar current collector overlap.

[0056] The battery also includes tabs, and one tab is shared between any two adjacent bipolar electrodes;

[0057] When the tab connection areas disposed opposite to each other between adjacent bipolar electrodes are positive tab 10 connection areas, a positive tab 10 is inserted between the two positive tab 10 connection areas, and both sides of the positive tab 10 are connected to the two positive tab 10 connection areas respectively;

[0058] When the tab connection regions disposed opposite each other between adjacent bipolar electrodes are the negative tab 8 connection regions, a negative tab 8 is inserted between these two negative tab 8 connection regions, and both sides of the negative tab 8 are respectively connected to the two negative tab 8 connection regions.

[0059] Among them, the connection between the tab and the tab connection region can be achieved by using a conductive adhesive 9 or welding.

[0060] The conventional assembly method of bipolar electrodes in a battery is to arrange the positive and negative electrodes of two adjacent bipolar electrodes opposite to each other. A separator still needs to be provided between the positive and negative electrodes to achieve electronic insulation and ionic conduction, so that the positive and negative electrodes of two adjacent bipolar electrodes form a primary battery.

[0061] In the solution of the present application, the base film layer 1 in the bipolar electrode is designed as a polymer film layer plus ceramic layers 2 on both sides to form a sandwich structure. Then, a copper layer 4 and an aluminum layer 3 are plated on the surface of the base film layer 1. The bipolar current collector is provided with micro-channels 7 through which lithium ions can pass along the thickness direction, and the micro-channels 7 penetrate through the aluminum layer 3, the base film layer 1, and the copper layer 4; as Figure 4 shown, taking charging as an example, lithium ions at the positive electrode can diffuse in any direction up and down and can be embedded into the negative electrode. Taking discharging as an example, lithium ions at the negative electrode can be deintercalated in any direction up and down and can return to the positive electrode; such a current collector has two functions:

[0062] (1) Provide current output channels for the positive electrode active material and the negative electrode active material;

[0063] (2) Instead of the conventional separator structure, the positive and negative electrodes of a single bipolar electrode can form a primary battery.

[0064] Such a design can produce the following effects: eliminating the separator structure significantly improves the volumetric energy density in the battery; eliminating the separator lamination process improves production efficiency, and at the same time avoids the risk of short circuit at the edges of the positive and negative electrode active material layers 6 caused by the alignment error in the lamination process; there are multiple diffusion channels for lithium ions in the battery, reducing the battery internal resistance and improving the rate performance.

[0065] The tab connection method of the conventional bipolar electrode is that each bipolar electrode needs to be connected to a positive tab 10 and a negative tab 8, with high process costs. And the tabs are generally metal foils with a relatively high density, which is not conducive to achieving the lightweight and cost reduction of power batteries. In the solution of the present application, any two bipolar electrodes are arranged with the same polarity opposite to each other, and a tab is inserted therein, so that two bipolar electrodes can share a positive tab 10 or a negative tab 8, greatly improving the utilization rate of the tabs and the battery energy density; at the same time, it also balances the current between any two adjacent bipolar electrodes, improves the consistency of the current density in the battery, and is beneficial to the extension of the battery cycle life.

[0066] In this application, a ceramic layer 2 is added on both sides of the polymer film layer. The ceramic layer 2 and the polymer base film together form a structure equivalent to the "separator" in a traditional lithium

[0067] battery (but different from directly using a separator, with completely different setting positions and structural relationships). Its function is to isolate electron transmission while allowing ions to pass through, so as to ensure that lithium ion deintercalation can occur between the positive and negative electrodes in the battery without internal short circuit. Therefore, three basic functions are required: 1. There are pores that can allow ions to pass through; 2. Electron insulation; 3. It will not easily shrink when heated (to avoid pore deformation or reduction in the planar dimension due to shrinkage, resulting in contact short circuit between the positive and negative electrodes). The ceramic layer added on both sides of the polymer film layer in this application can not only enhance the second function but also achieve the third function (the first function is achieved by punching as described above); on the other hand, the bonding force between the polymer base film and the metal layer is usually weak. Therefore, in the solution of this application, setting the ceramic layer between them can also improve the bonding strength between the polymer base film and the metal layer, so it has multiple advantageous effects.

[0068] In some embodiments, on the surface of the base film layer 1 where the aluminum layer 3 is provided, the aluminum layer 3 only covers a part of the surface of the base film layer 1, and the area of the base film layer 1 not covered by the aluminum layer 3 extends beyond the connection area of the positive electrode tab 10; on the surface of the base film layer 1 where the copper layer 4 is provided, the copper layer 4 only covers a part of the surface of the base film layer 1, and the area of the base film layer 1 not covered by the copper layer 4 extends beyond the connection area of the negative electrode tab 8; as Figures 1-3 shown, the connection areas of the positive electrode tab 10 and the negative electrode tab 8 are respectively set at the end regions of the metal layer on the base film layer 1. Here, the end of the metal layer is not flush with the inner base film layer 1, but the edge end of the base film layer 1 extends beyond the edge end of the metal layer, leaving a part of the blank base film layer 1; the positive and negative electrodes of this application are integrated on one pole piece. At the end of the current collector, arc short circuit may occur because the distance between the positive and negative current collectors (i.e., the copper layer 4 and the aluminum layer 3) is too close (micrometer level). Therefore, in this solution, the polymer film is designed such that only a part of its surface is covered by copper and aluminum, and the uncovered area is the edge area beyond the electrode tab welding area. In this way, the polymer film can act as an insulator, increasing the arc distance between the copper and aluminum layers 3 and reducing the risk of arc short circuit; and this extended polymer film can also provide special protection. For example, when the battery is externally squeezed, the positive and negative active material layers 6 may overflow from the edges of the copper layer 4 or the aluminum layer 3 due to the extrusion, resulting in the positive and negative active material layers 6 coming into contact and short circuiting at the edges, causing the battery to get out of control; the solution of this application designs the polymer film to extend beyond the edges of the copper layer 4 and the aluminum layer 3, which can add an additional line of defense between the positive and negative active materials that overflow to the edges of the copper layer 4 and the aluminum layer 3 due to extrusion, reducing the risk of short circuit of the positive and negative active materials caused by extrusion.

[0069] In some embodiments, the tab is a full tab, and the width of the tab is the same as the width of the bipolar electrode; since the design of the solution of the present application can reduce the number of tab pieces, the pressure on the tab width design can be reduced. Making the width of each tab larger can improve the current collector's conductivity, reduce the internal resistance, and reduce the heat accumulation caused by overcurrent heating.

[0070] In some embodiments, the connection regions of any two adjacent bipolar electrodes and the same tab shared between them do not completely overlap; in the preferred embodiment, the connection regions of any two adjacent bipolar electrodes and the same tab shared between them are staggered; because two bipolar electrodes share a tab, if they are connected by conductive adhesive 9, it is necessary to avoid the complete overlap of the two layers of conductive adhesive 9. Because if fully charged, the multi-layer electrode sheets may accumulate too thickly at the place where the conductive adhesive 9 is coated in the thickness direction, which is not conducive to the subsequent tab bundling; if they are connected by welding, the two weld marks should also be avoided from completely overlapping to avoid welding fatigue caused by multiple welds at the same position of the tab and reduce the decrease in welding reliability caused by welding fatigue.

[0071] In some embodiments, on the projection plane perpendicular to the thickness direction of the bipolar current collector, the tab does not overlap with the active material layers between the two adjacent bipolar electrodes where the tab is located; the positive tab 10 does not overlap with the positive active material layer 5, and the negative tab 8 does not overlap with the negative active material layer 6, in order to avoid scratching the active material when the tab pierces the active material layer due to manufacturing tolerances during the tab connection process.

[0072] The technical solution of the present invention will be further described in detail below in conjunction with specific embodiments:

[0073] Example 1

[0074] A bipolar current collector is prepared as follows:

[0075] (1) Coating a ceramic slurry mainly composed of boehmite (the ceramic slurry contains 55% w / w of boehmite main material, 10% w / w of binder polyvinyl alcohol, 0.5% w / w of dispersant polyethylene glycol, and 34.5% w / w of solvent water) on a 4.5-μm PET film, and performing a drying treatment to form a 1-μm-thick ceramic layer to obtain a base film;

[0076] (2) Obtaining a current collector with one-sided copper plating on one side of the base film through magnetron sputtering and electroplating;

[0077] (3) Obtaining a semi-finished bipolar current collector with one side copper-plated and the other side aluminum-vapor-deposited on the other side of the base film;

[0078] (4) Laser drill the bipolar current collector semi-finished product to make micropores for lithium ion transmission evenly distributed on the surface of the current collector, obtaining a bipolar current collector. The aperture of the micropores is 20 μm, and the pore spacing between adjacent pores is 200 μm;

[0079] In the magnetron sputtering process of step (2), it includes: attaching a mask to one side of the base film, and the attached mask is fixed at least at one end edge of the base film; feeding the base film and the mask into the magnetron sputtering equipment to perform magnetron sputtering copper plating of 40 nm, and removing the mask after plating; then immersing it in an electroplating bath to thicken the copper layer by electroplating to 4 to 1 μm, obtaining a current collector semi-finished product with unilateral partial copper plating;

[0080] In the evaporation process of step (3), it includes: attaching a mask to the other side of the base film (i.e., the side with the copper layer 4), and the attached mask is fixed at least at one end edge of the base film; feeding the base film and the mask into the vacuum evaporation equipment to perform evaporation aluminum plating of 1 μm, and removing the mask after plating, obtaining a semi-finished current collector.

[0081] Example 2

[0082] A bipolar electrode, the preparation process is as follows:

[0083] (1) Prepare the positive electrode material: Mix 98 wt% nickel cobalt manganese 811 (NCM811) with 1 wt% carbon nanotubes and 1 wt% super P, and obtain a preliminary material after ball milling at 500 rpm for 2 h; Mix 98 wt% of the preliminary material and 2 wt% of PTFE by mass fraction, ball mill at 500 rpm for 2 h at 5 °C, and then stand still in an environment of 50 °C for 1 h to obtain a positive electrode mixture; Prepare the negative electrode material: Mix 99 wt% graphite with 1 wt% SP, and obtain a preliminary material after ball milling at 500 rpm for 2 h; Mix 98 wt% of the preliminary material and 2 wt% of PTFE by mass fraction, ball mill at 500 rpm for 2 h at 5 °C, and then stand still in an environment of 50 °C for 1 h to obtain a negative electrode mixture;

[0084] (2) After mixing the positive electrode material evenly, roll it to obtain a positive electrode self-supporting film; After mixing the negative electrode material evenly, roll it to obtain a negative electrode self-supporting film;

[0085] (3) Attach the positive electrode self-supporting film to the surface of the aluminum layer part of the bipolar current collector prepared in Example 1; Attach the negative electrode self-supporting film to the surface of the copper layer part of the bipolar current collector and dry it, and obtain a finished bipolar electrode after cutting;

[0086] Example 3

[0087] A battery, the assembly process is as follows:

[0088] (1) Alternately stack multiple bipolar electrodes prepared in Example 2, with one positive electrode facing up and one negative electrode facing up;

[0089] (2) Insert the positive electrode tab between two bipolar plates opposite to the positive electrode, and connect it to the positive electrode tab connection areas of the two bipolar plates; insert the negative electrode tab between two bipolar plates opposite to the negative electrode, and connect it to the negative electrode tab connection areas of the two bipolar plates; the tabs are made of metal foil.

[0090] (3) Bundle multiple positive electrode tabs and weld them to the positive electrode post; bundle multiple negative electrode tabs and weld them to the negative electrode post, then place them in the battery case, inject the electrolyte (using a LiPF6 solution as the electrolyte, with the solvent being a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1, and adding 2 wt% of vinylene carbonate as an additive to obtain the electrolyte), and seal it to obtain the battery.

[0091] In the positive electrode tab connection process of step (2), it includes: coating conductive adhesive on partial areas on both the front and back sides of the positive electrode tab to form a first conductive adhesive area and a second conductive adhesive area, inserting the positive electrode tab between two bipolar plates opposite to the positive electrode, and bonding the first conductive adhesive area and the second conductive adhesive area to the positive electrode tab connection areas of the two opposite bipolar plates respectively. The first conductive adhesive area and the second conductive adhesive area do not completely overlap, and the positive electrode tab does not contact the positive electrode active material layers of the two opposite bipolar plates.

[0092] In the negative electrode tab connection process of step (3), it includes: coating conductive adhesive on partial areas on both the front and back sides of the negative electrode tab to form a third conductive adhesive area and a fourth conductive adhesive area, inserting the negative electrode tab between two bipolar plates opposite to the negative electrode, and bonding the third conductive adhesive area and the fourth conductive adhesive area to the negative electrode tab connection areas of the two opposite bipolar plates respectively. The third conductive adhesive area and the fourth conductive adhesive area do not completely overlap; the negative electrode tab does not contact the negative electrode active material layers of the two opposite bipolar plates.

[0093] Perform battery energy density, DC impedance test, and high-temperature cycle performance test on the battery prepared in Example 3, and the test results are shown in Table 1.

[0094] Comparative Example 1

[0095] Using a conventional lithium battery, in this battery, the positive current collector uses a 4.5-μm PET film with aluminum layers on both sides, and a positive active material layer (with the same formulation as the positive electrode material in Example 2) is provided on the surface of the aluminum layers to obtain a positive electrode sheet; the negative current collector is a 4.5-μm PET film with copper layers on both sides, and a negative active material layer (with the same formulation as the negative electrode material in Example 2) is provided on the surface of the copper layers to obtain a negative electrode sheet; the preparation processes of the copper layer and the aluminum layer on the current collector are the same as those in Example 1; the separator uses a ceramic separator, the base film is a 6-μm PP film, and both sides are boehmite ceramic layers with a thickness of 1 μm and a porosity of 50%; the battery assembly process is as follows: stack the above positive electrode sheet, separator, negative electrode sheet, and separator repeatedly, and weld current collectors for leading out current on the surfaces of both sides of each electrode sheet to obtain an electrode core; bundle multiple positive current collectors and weld them to the positive electrode terminal; bundle multiple negative current collectors and weld them to the negative electrode terminal, install them into the battery case, inject electrolyte (with the same electrolyte formulation as in Example 3), and encapsulate to obtain the battery.

[0096] Perform battery energy density, DC impedance test, and high-temperature cycle performance test on the battery prepared in Comparative Example 1, and the test results are shown in Table 1.

[0097] Comparative Example 2

[0098] In this comparative example, ceramic layers are not provided on the surfaces of both sides of the polymer film layer. Instead, an aluminum layer is directly provided on one surface of the polymer film layer and a copper layer is provided on the other surface. The polymer film layer uses a 5-μm PET film; other aspects are the same as in Examples 1-3, including the same punching treatment, to prepare a bipolar electrode.

[0099] Perform battery energy density, DC impedance test, and high-temperature cycle performance test on the battery prepared in Comparative Example 2, and the test results are shown in Table 1.

[0100] Test description:

[0101] (1) Energy density test:

[0102] Measure the diameter and height of the electrode core before it is put into the case, calculate its volume V0, and then assemble it to obtain a cylindrical battery. In a normal temperature environment, charge and discharge the lithium-ion batteries prepared in the examples and comparative examples at a current of 0.33C for the first time. The charging is constant current and constant voltage charging, the termination voltage is 4.2V, the cut-off current is 0.05C, the discharge termination voltage is 2.5V, and leave it for 12h; charge at a current of 1C with constant current and constant voltage charging, the termination voltage is 4.2V, the cut-off current is 0.05C; discharge at a current of 1C, the discharge termination voltage is 2.5V, and record the discharge capacity C0 of the electrode core. The battery volume energy density = discharge capacity C0 / electrode core volume V0.

[0103] (2) High-temperature cycle performance test:

[0104] At 50 °C, the test object is subjected to a cyclic test according to the following procedure: The sample battery after formation is fully charged at a rate of 1C (i.e., constant current charging until 4.2V and then constant voltage charging until the current reaches 0.05C and then cutoff), fully discharged (i.e., constant current discharging until 3.0V and then constant voltage discharging until the current reaches 0.05C and then cutoff). One charge-discharge cycle is one cycle. After 200 cycles, record its full charge capacity, divide it by its first full charge capacity, and the capacity retention rate after 200 cycles is obtained.

[0105] (3) DC impedance test:

[0106] At 25 °C, the test object is charged and discharged to 50% SOC, discharged at a current of 1C for 18 seconds, record the battery voltage U2, current I before the discharge stops, and the battery voltage U1 after the battery voltage stabilizes. Calculate according to the formula R = (U2 - U1) / I to obtain the DC internal resistance R.

[0107] Table 1

[0108]

[0109] As can be seen from the above table:

[0110] The volume energy density of the battery prepared by the method of this application is higher than that of the conventional lithium battery in Comparative Example 1, while the DC internal resistance of the battery is lower than that of the conventional lithium battery, and the high-temperature cycle results are equivalent to those in Comparative Example 1; the capacity retention rate after 200 cycles at a high temperature of 50 °C is higher than that of Comparative Example 2 without the ceramic layer added on both sides of the polymer film layer, and the differences in battery energy density and DC impedance test are not significant.

[0111] Therefore, considering the performance data in all aspects above, the embodiments of this application are significantly better and can bring better use effects and product values.

[0112] The above is only a preferred embodiment of the present invention, and it does not impose any form of limitation on the present invention. Any person skilled in the art, without departing from the technical solution scope of the present invention, based on the technical essence of the present invention, any simple modification, equivalent replacement, and improvement made to the above embodiments still fall within the protection scope of the technical solution of the present invention.

Claims

1. A bipolar current collector, characterized in that: It comprises a base film layer, wherein one side surface of the base film layer is provided with an aluminum layer, and the other side surface is provided with a copper layer; The base film layer includes a middle polymer film layer and ceramic layers on both sides of the polymer film layer; The bipolar current collector is provided with micro channels for lithium ions to pass through distributed along the thickness direction, and the micro channels penetrate the aluminum layer, the base film layer and the copper layer.

2. A method for preparing a bipolar current collector, characterized in that: The following steps are involved: Ceramic slurry is coated on both sides of the polymer film and dried to obtain a base film layer; A copper layer is formed on one side of the base film layer and an aluminum layer is formed on the other side of the base film layer to obtain a semi-finished bipolar current collector; The bipolar current collector semi-finished product is laser-drilled so that micro channels penetrating the aluminum layer, the base film layer and the copper layer are evenly distributed on the semi-finished product.

3. A bipolar electrode, characterized in that: A bipolar current collector comprising the method of claim 1 or claim 2, further comprising a positive electrode active material layer and a negative electrode active material layer, wherein the positive electrode active material layer is disposed on the outer surface of the aluminum layer, and the negative electrode active material layer is disposed on the outer surface of the copper layer; The outer surface of the aluminum layer is divided into a positive electrode ear connection area, and the positive electrode ear connection area is not provided with a positive electrode active material layer; the outer surface of the copper layer is divided into a negative electrode ear connection area, and the negative electrode ear connection area is not provided with a negative electrode active material layer.

4. The bipolar electrode according to claim 3, characterized in that: On the surface of the base membrane layer where an aluminum layer is provided, the aluminum layer only covers part of the surface of the base membrane layer, and the area of ​​the base membrane layer not covered by the aluminum layer exceeds the positive electrode ear connection area; on the surface of the base membrane layer where a copper layer is provided, the copper layer only covers part of the surface of the base membrane layer, and the area of ​​the base membrane layer not covered by the copper layer exceeds the negative electrode ear connection area.

5. A battery, characterized in that: It comprises at least one bipolar electrode as claimed in claim 3 or 4; when there are multiple bipolar electrodes, the bipolar electrodes are stacked in sequence, and the active material layers arranged relatively between any two adjacent bipolar electrodes are active material layers of the same polarity.

6. The battery according to claim 5, characterized in that: In the plurality of bipolar electrodes stacked in sequence, the positive electrode tab connection regions overlap on a projection plane perpendicular to the thickness direction of the bipolar current collector, and the negative electrode tab connection regions overlap on a projection plane perpendicular to the thickness direction of the bipolar current collector.

7. The battery according to claim 5, characterized in that: It also includes a pole ear, and any two adjacent bipolar electrodes share one pole ear; When the tab connection regions opposite to each other between adjacent bipolar electrodes are positive tab connection regions, a positive tab is inserted between the two positive tab connection regions, and two sides of the positive tab are respectively connected to the two positive tab connection regions; When the tab connection regions opposite to each other between adjacent bipolar electrodes are negative tab connection regions, a negative tab is inserted between the two negative tab connection regions, and two sides of the negative tab are respectively connected to the two negative tab connection regions.

8. The battery according to claim 7, characterized in that: The pole lug is a full pole lug, and the width of the pole lug is consistent with the width of the bipolar electrode.

9. The battery according to claim 7, characterized in that: The connection area between any two adjacent bipolar electrodes and the same electrode ear shared between them does not completely overlap.

10. The battery according to claim 7, characterized in that: On a projection plane perpendicular to the thickness direction of the bipolar current collector, the electrode tab does not overlap with the active material layer between two adjacent bipolar electrodes where the electrode tab is located.

Citation Information

Cited By

  • Composite current collector, bipolar pole piece and bipolar battery

    CN121172141A

  • Multi-layer flexible circuit board and preparation method thereof

    CN121174374A

  • A multilayer flexible wiring board and a method for manufacturing the same

    CN121174374B